The phenomenon of B. Pascal in the European context: a view from the shore of historico-philosophical Ukrainian studies - Horskyi, Vilen (Sententiae, 2000)
The article is devoted to the problem of belonging of Ukrainian philosophy to the European tradition. The author states that Pascal's doctrine is non-ratio-centered and, therefore, does not correspond to the leading trends of European modern philosophy. At the same time, this doctrine is considered to be one of the most important for the development of the Modern tradition (including contemporary discussions between postmodernist and communicative philosophy thinkers). Thereafter the author concludes that modern philosophy is at least not monistic. The same non-monistic nature is also evident in the European history of ideas before the 17th century: the cleavage between Athens and Jerusalem, Latin and Greek theology, etc. This non-monism is manifested in the existence of at least two defining trends in European philosophy: the rational-centered one and the one that prefers a cordial attitude to the world and an approach of an intellectual contemplation. At the same time, the author notes that with the transition to lower levels of generalization, this dualism will increasingly appear to be a true pluralism of the European intellectual tradition. Based on the recognition of the content originality of national philosophies, the author attributes Ukrainian philosophy primarily to the second of the outlined trends. On the basis of the dominance of cordocentric orientations in Ukrainian philosophy, he rejects the arguments that interpret Ukrainian philosophy as fundamentally non-European.